Regulation of cytokine-inducible SH2-containing protein (CIS) by ubiquitination and Elongin B/C interaction - Jensik, Philip J. (Mol Cell Endocrinol, 2014)
Cytokine-inducible SH2-containing protein (CIS) inhibits prolactin receptor (PRLR) signaling and acts as part of an E3 ubiquitin ligase complex through interactions with Elongin B/C proteins. This study aimed to identify CIS lysine ubiquitination sites and determine roles of ubiquitination and Elongin B/C interactions on CIS protein stability and PRLR signaling inhibition. Site-directed mutations revealed that CIS can be ubiquitinated on all six lysine residues. Elongin B/C interaction box mutation had no influence on CIS ubiquitination. CIS stability was increased by mutation of lysine residues and further enhanced by co-mutation of Elongin B/C interaction domain. CIS inhibition of STAT5B phosphorylation and casein promoter activation was dependent on CIS interactions with Elongin B/C, but not on CIS ubiquitination. These data indicate CIS protein stability is regulated through multiple mechanisms, including ubiquitination and interaction with Elongin B/C proteins, whereas CIS functional inhibition of PRLR signaling is dependent on the Elongin B/C interaction.